Multi-criteria evaluation of a 1.5 ton 3-roller village level stationary and mobile cane mill systems using sweet sorghum for bioethanol production in Ilocos Norte - Layaoen, Haerold Dean Z.
This study was conducted to determine the most efficient and cost-effective means of producing a processed feedstock from sweet sorghum for bioethanol production under a village level processing in Ilocos Norte.Qualitative criteria such as ease of use, maintainability and the like as well as quantitative factor like cost were used in the analysis and evaluation of both production systems with stationary and mobile cane mills. Consultations with the stakeholders were carried out to elecit the weights ascribed to the different criteria. Results showed that 25% of the weights pertain to the qualitative factors while the rest is accounted for by cost. This ratio is very much reflective of most of the evaluations dealing with agro-industrial ventures. Analysis of the qualitative factors through factor rating revealed that each system is not significantly different from each other. On the other hand, cost analysis showed very significant differences depending on certain conditions such as distance of the farm to processing area, mode of transportation and others. Seven (7) cost-distance models were generated to represent these varying cases. The models were then analyzed and evaluated based on the total and per unit weight production cost criterion. At current condition, since the yield between the two systems varies, the production cost per unit weight criterion was the basis of the decision process. based on the results, the production system with mobile cane mill is more efficient and cost-effective than the system with stationary cane mill regardless of the biomass source distance from the processing area. This is because the cost per unit weight of pasteurized juice incurred by the system with stationary cane mill is greater by 25% than in the mobile cane mill. based on effective juice yield, the stationary cane mill had 27.13% by total stalk weight while the mobile cane mill had 34.6%. Stalk cost contributes about 60% of the total production cost therefore the influence of the resulting per unit cost of extracted juice on the total cost behavior is high. If both production systems exhibit similar effective yield, cost-distance graph for total and unit production cost for both systems would be consistent as illustrated in the simulated cases, thus, their cost curves intersect exposing a range of distance in which each alternative is advantageous.